Production management model based on Lean manufacturing and SLP to optimize unproductive times in SMES in the plastics industry - Seminario Mallqui, Oscar Jofre (2023)
In recent years, there has been a considerable increase in demand from the plastics industry, so many SMEs have not been able to meet their demands due to production problems, since there is a high number of unproductive hours in unnecessary movements, machine stoppage, poor machinery maintenance planning, among others. The problem that has been identified and that occurs in the majority of SMEs in the plastics sector is low availability due to unproductive times. The objective of this article is to reduce downtime in production and consequently increase OEE, since this represents a loss of money for the company, especially in the injection process. To this end, the implementation of the Lean Manufacturing model is proposed, validated with its TPM, 5s, ErgoSMED and Poka Yoke tools, in addition to the implementation of SLP. To validate this improvement proposal, the Arena simulation software was used in a company in the plastics sector, since it will be possible to obtain a reduction in unproductive times by 20%, reduce travel times by 25%, reduce the labor disorder in jobs by 15%, and in general increase availability by 12%, thus increasing the OEE indicator by 20%.